Development and decline of Russian cities: reasons and possible solutions - V. B. Zotov (Вестник университета)
This article discusses the problems of urbanization and the development of megacities against the backdrop of the decline of medium and small towns in the Russian Federation. For the assessment, materials from the official website of Rosstat, as well as expert data and materials from consulting companies for 2021-2022 were used. In the course of the study, it was found that megalopolises receive predominant development in modern conditions, as evidenced by the practice of construction. The existing instruments of state support for the development of medium and small towns are either of little use or ineffective. Based on the results of the study, it is concluded that it is necessary to change the situation for the development of medium and small towns in Russia, to develop new approaches and to apply complex solutions to the existing problem. The author proposes various tools of an economic, managerial, organizational nature to overcome a crisis situation.